Glaucoma laser treatments: modern approaches and practice guidelines - M.H. Rabadanova; Zh.G. Oganezova; E.A. Egorov; D.V. Katz; V.V. Novoderezhkin (РМЖ "Клиническая офтальмология")
M.H. Rabadanova1,2, J.G. Oganezova1,3, E.A. Egorov1, D.V. Katz2, V.V. Novoderezhkin2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Municipal Clinical Hospital No. 15 named after O.M. Filatov, Moscow, Russian Federation 3Research Center for Medical Genetics, Moscow, Russian Federation Glaucoma represents a significant medical, economical, and social burden for the healthcare system both in Russia and worldwide. Despite a variety of pharmacological, surgical and laser treatment options, the number of patients with irreversible glaucomatous damage to visual function is continuously rising. Currently, more emphasis has been made on laser micropulse techniques for the treatment of glaucoma. It is underpinned by several important advantages of this modality: it has demonstrated high efficacy; can be performed in outpatient settings without general anesthesia; is well-tolerated by patients; can be repeated over time and combined with surgeries; and is considered as a cost-effective treatment. There are different laser treatment options: laser trabeculoplasty, iridogonioplasty, laser iridectomy, goniopuncture, and laser cyclodestructive procedures, as well as their modifications. The article discusses specific features of these techniques, indications and contraindications, and laser characteristics. The article emphasizes the role of gonioscopy as an effective ocular assessment technique helping to create an individualized laser treatment plan for glaucoma patients. Also, the article focuses on pre- and postoperative management of patients and presents an algorithm for the management of patients with different glaucoma forms referred to the laser treatment. Keywords: glaucoma, gonioscopy, micropulse laser treatment, pre-operative management, intraocular pressure, pigment dispersion syndrome, trabeculoplasty, iridogonioplasty, iridectomy, goniopuncture, cyclocoagulation, bromfenac. For citation: Rabadanova M.H., Oganezova J.G., Egorov E.A. et al. Glaucoma laser treatments: modern approaches and practice guidelines. Russian Journal of Clinical Ophthalmology. 2022;22(4):265–272 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-265-272.